Inverse Design of Local Solar Flux Distribution for a Solar Methanol Reforming Reactor Based on Shape Optimization - Tang, Xinyuan; Yang, Weiwei; Dai, Zhouqiao; Yang, Yongjian (Frontiers in Energy Research, 2022)
In this work, an inverse design method that coupling the multiphysics model for a solar trough thermochemical reactor (SPTR) and shape optimization model is proposed to find out optimal solar flux distribution for maximizing overall reactor performance. Gradient-based segmentation method is applied to convert the continuous solar flux into step-like flux to guide the concentrator system design. Performance comparisons among uniform flux, linear decreasing flux and the optimized non-linear flux are also conducted to discuss the reliability of SPTR performance improvement. The results show that the optimized non-linear solar flux can improve the methanol conversion, solar thermochemical conversion and hydrogen yield of SPTR by 2.5%, 3.3% and 2.4%, respectively, compared with the uniform flux. This is attributed to the fact that the optimized non-uniform flux distribution enhances the synergy between temperature and reaction fields, and achieves a better match between spatial solar flux supply and local energy demand by reactions. Also, it is shown that the optimized step-like flux by regressing the optimized non-linear flux can perfectly keep SPTR performance, and is effective in boosting SPTR performance under different operating conditions.